OBSCENE TRAFFIC - Schettini, Laura. ([S.l.])
1 online resource.
Keywords: This book explores the early globalization of prostitution from the perspective of the Italian case. It is a story of prostitution, migration, and work, built through analyses of primary sources (the Italian archive of International Police) and covering a wide chronological period, from the end of the nineteenth century through the Second World War. It is the story of Giuseppa, Virginia, and many others who embarked from Italian ports in the 1890s to work in brothels in Egypt, Libya, and Malta, but also that of Marguerite, one of the numerous foreign prostitutes working in Italy in the 1930s. It is the story of Mariella, forced by her husband Beniamino to work as a prostitute in the United States while pregnant in the 1900s, of Francesco, who on the eve ofthe Second World Warrecruited young natives to work in his cabarets in Panama. It is the story of a passionate diplomat committed to the League of Nations' fight against the white slave traffic but also of police officers, consuls, and ministers more concerned about their nation's reputation than women's rights. This book, aimed at students, scholars and non-profit organizations, illustrates the complexity of the world of prostitution as it transformed into a transnational market, its links with migration processes and colonial expansion, as well as its relevance as a (inter-)national political issue.